90 years of freedom –after Summerhill: what happened to the pupils of Britain’s most radical school? - Lucas, Hussein (Revista Hipótese, 2018)
In this paper, the author brings highlights from his book “After Summerhill”. Its main purpose is to describe the main concepts about Summerhill education and to find out is outcomes. In short, the author seeks to answer “what happened to the pupils”.
Keywords: Summerhill; Freedom; Neill